2018
DOI: 10.1186/s13550-018-0466-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of reconstruction protocol for histo-biological characterisation of breast cancers using FDG-PET radiomics

Abstract: BackgroundThe aim of this study is to determine if the choice of the 18F-FDG-PET protocol, especially matrix size and reconstruction algorithm, is of importance to discriminate between immunohistochemical subtypes (luminal versus non-luminal) in breast cancer with textural features (TFs).ProceduresForty-seven patients referred for breast cancer staging in the framework of a prospective study were reviewed as part of an ancillary study. In addition to standard PET imaging (PSFWholeBody), a high-resolution breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Nonetheless, because a high ICC also indicates that features can differentiate well between inserts, our results suggest that EARLcompliant reconstructions also result in more meaningful features, especially when using the EARL2 settings. This is in line with the findings of Aide et al, who showed that images reconstructed with higher-resolution reconstructions improved the characterization of breast tumors when compared with EARL1 (22).…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, because a high ICC also indicates that features can differentiate well between inserts, our results suggest that EARLcompliant reconstructions also result in more meaningful features, especially when using the EARL2 settings. This is in line with the findings of Aide et al, who showed that images reconstructed with higher-resolution reconstructions improved the characterization of breast tumors when compared with EARL1 (22).…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we found 44 papers evaluating technical factors [ 53 , 60 , 61 , 62 , 64 , 154 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 , 327 , 328 , 329 , 330 , 331 , 332 , 333 , 334 , 335 , 336 , 337 , 338 , 339 ], without pursuing a clinical objective. Of these, 30% evaluated the impact of different tumor segmentation methods.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the image reconstruction methods on the texture analysis of dbPET should also be clarified in the future. High-resolution reconstruction of PET/CT images has been reported to change the textural features compared to standard reconstructed clinical PET images (11,25). It is necessary to assess how the texture features of dbPET change compared to that of the whole-body PET/CT image due to the differences in the reconstruction method.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, research on radiomics has focused particularly on texture analysis using various imaging modalities, including BC studies utilizing MRI and US (7,8). Some studies reported that PET images' texture features are associated with BC subtypes and prognosis (9)(10)(11). Texture analysis, which assesses intra-tumoral heterogeneity to compute image-specific information, is highly reproducible, has little variation among diagnostic radiologists, and will help mitigate the shortage of said radiologists who are excellent at diagnosing BC imaging.…”
Section: Introductionmentioning
confidence: 99%